The Politeness of Arabic’s Ethnic Community in Pekalongan City in The Domain of Commerce (Universitas Negeri Semarang, 2019)
Pekalongan City community is a multi-ethnic society. The multi-ethnic community interaction of Pekalongan City raises various language problems, one of them is in terms of language politeness. This study was described the adherence to the principle of linguistic politeness and the violation of the principle of linguistic politeness in the people of Pekalongan, an ethnic Arabic City in the realm of commerce. The data in this study were collected by the simulations method, while the data analysis was carried out using ethnographic methods. The form of adherence to the principle of politeness in the urban community of Pekalongan ethnic Arabs in the realm of trade includes thimble rather than blasphemy, generosity, indulgence, approval, and conciliation. The form of violation of the principle of linguistic politeness in the realm of trade carried out by the people of Pekalongan City, the ethnic Arab includes modesty maxim and agreement maxim.